Song of the water boatman : & other pond poems - Sidman, Joyce; Prange, Beckie (Boston : Houghton Mifflin, 2005)
A collection of poems that provide a look at some of the animals, insects, and plants that are found in ponds, with accompanying information about each.
Listen for me -- Spring peepers -- Spring splashdown -- Wood duck -- Diving beetle's food-sharing rules -- Great diving beetle -- Fly, dragonfly! -- Green darner -- In the depths of the summer pond -- Food chain -- A small green riddle -- Duckweed -- Aquatic fashion -- Caddis fly -- Song of the water boatman and backswimmer's refrain -- Water boatman, backswimmer -- Travel time -- Water bear -- The season's campaign -- Cattails -- Into the mud -- Painted turtle.
Keywords: Pond animals -- Juvenile poetry; Ponds -- Juvenile poetry; Children's poetry, American; Pond animals -- Poetry; Pond plants -- Poetry; American poetry